TAX SOCIALIZATION, TAX INCENTIVES, AND TAX SANCTIONS ON TAXPAYER COMPLIANCE AND TRUST IN TAX INSTITUTIONS AS MODERATING VARIABLES - Durrotul Mufidah; Syaiful Syaiful (PT. Antis International Publisher, 2024)
The purpose of this research is to study the influence of tax socialization, tax incentives, tax sanctions and trust in taxation institutions on taxpayer compliance, as well as the moderating role of trust in taxation institutions in strengthening the influence of tax socialization, tax incentives, and tax sanctions on taxpayer compliance. Data were collected through a survey of one hundred people who are taxpayers in Gresik. The results of the analysis show that tax socialization and tax incentives do not have a significant influence on taxpayer compliance, while tax sanctions have a positive influence on taxpayer compliance. In addition, trust in taxation institutions is also unable to strengthen the influence of tax sanctions on taxpayer compliance. These findings indicate that although trust in tax institutions is an important factor, it is not strong enough to increase taxpayer compliance through socialization, incentives, or sanctions. Therefore, a more comprehensive approach is needed in designing effective tax policies. Recommendations to improve taxpayer compliance include improving the quality and relevance of tax socialization, simplifying the process and increasing the accessibility of tax incentives, and stricter and more consistent law enforcement. This research contributes to the tax literature by highlighting the role of trust in tax institutions and suggesting more effective policies to improve taxpayer compliance.